2015
DOI: 10.5901/jesr.2015.v5n2p137
|View full text |Cite
|
Sign up to set email alerts
|

Global Leadership Competencies

Abstract: This paper explores the conceptualization of global leadership and identification of global leadership competencies. It attemptsto answer what are the competencies for global leadership? Researchers indicated that global leaders require a unique set of global leadership competencies to effectively fulfil their roles. They further identified seven competencies for global leaders that include: (1) culture awareness and sensitivity, (2) global mindset or perspectives, (3) learning from experiences, (4) developing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In more recent researches conditioned by globalization processes the intercultural dimension of leadership competences is observed more and more distinctly. Summarising the ideas of the discussed authors, we can specify leadership competencies identified as fundamental (Hassanzadeh et al, 2015;Hooper & Potter, 2019;Iordache-Platis, 2017;Kessler, 2020;Kazakevych, 2020;Ruben, 2019). First of all, it is communicative skills/ language proficiency viewed in intercultural dimension.…”
Section: Problem Statementmentioning
confidence: 99%
“…In more recent researches conditioned by globalization processes the intercultural dimension of leadership competences is observed more and more distinctly. Summarising the ideas of the discussed authors, we can specify leadership competencies identified as fundamental (Hassanzadeh et al, 2015;Hooper & Potter, 2019;Iordache-Platis, 2017;Kessler, 2020;Kazakevych, 2020;Ruben, 2019). First of all, it is communicative skills/ language proficiency viewed in intercultural dimension.…”
Section: Problem Statementmentioning
confidence: 99%
“…Transactional leadership significantly affected the effectiveness of leaders by way of combined efficiencies and transformative leadership was the most favored type of leadership [42] . The authors noted that, according to two presumptions, leadership is needed for project managers: first, leaders or project managers will dramatically affect the performance of team members and second, successful leaders inspire team members to achieve the related objectives of the organization [43,44] Tried to explore the correlation between both global leadership and the evolution of characteristics throughout practice and experience. Internationalization requires the active corporation of leaders to direct supporters to multiculturalism for overseas projects to become successful [39,45] .…”
Section: Domainmentioning
confidence: 99%
“…In a study of global leadership competency models, the researchers confirmed that nowadays, the most frequently mentioned global leadership competencies are intercultural skills and awareness (Park et al, 2017). Figure 2 is a recent attempt made by scholars to incorporate intercultural competency into the generic professional model (Hassanzadeh et al, 2015 Hassanzadeh et al (2015) In the above model, the traditional three-way division of attribute, knowledge and skill is maintained, but under each of these three categories, some intercultural elements are included, both implicitly and explicitly. The advantage of such model is that it retained the traditional division of competency clusters and thus make it easier to understand, however, it has not accentuated the intercultural competency enough.…”
mentioning
confidence: 94%